2021
DOI: 10.1007/s11625-021-00932-z
|View full text |Cite
|
Sign up to set email alerts
|

Fish out of water: consumers’ unfamiliarity with the appearance of commercial fish species

Abstract: Seafood labels play an increasingly key role in assisting consumers in purchasing processed and featureless fish products, and in encouraging sustainable fishing and aquaculture practices. While informed purchasing choices are typically influenced by traceability and labelling awareness, they also depend on the consumers’ ability to identify and discriminate the fish species available on the market, which to date remains notably unexplored. We asked 720 people across six European countries to identify pictures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Food fraud, while not a new phenomenon, has become more relevant in recent years, and seafood is one at the highest risk categories of foods [1]. Seafood fraud practices (including intentional mislabeling and species substitution) can take place at multiple points along the value chain, where fraudsters benefit from the fact that most consumers have difficulties to visually identify the product at species levels [2].…”
Section: Introductionmentioning
confidence: 99%
“…Food fraud, while not a new phenomenon, has become more relevant in recent years, and seafood is one at the highest risk categories of foods [1]. Seafood fraud practices (including intentional mislabeling and species substitution) can take place at multiple points along the value chain, where fraudsters benefit from the fact that most consumers have difficulties to visually identify the product at species levels [2].…”
Section: Introductionmentioning
confidence: 99%
“…The most famous cases were the horsemeat discovered in products labelled as beef [33] and the Halal meat, destined for Muslim consumers, containing pork meat [34]. Moreover, Cusa et al [35] showed that UK citizens are unfamiliar with the appearance of commercial fish species which could be reflected in a low interest in reading the labels on seafood. In the UK, there is evidence of a decline in fishmongers and fish counters in supermarkets [36] and a change in the (sea)food system to more processed products and replacement of counters with ready to go products (UPP, PPP) via supermarket shelves.…”
Section: Discussionmentioning
confidence: 99%